Analisis Kinerja Keuangan Usaha Agrowisata Yoga Barista di Desa Singapadu, Kecamatan Sukawati, Kabupaten Gianyar - I NYOMAN TRI ANANTA WIJAYA; I KETUT SUAMBA; PUTU UDAYANI WIJAYANTI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Financial Performance Analysis of Yoga Barista Agrotourism in SingapaduVillage, Sukawati District, Gianyar Regency Agrotourism is one type of agribusiness business. All types of businesses need tomake financial reports. Yoga Barista Agrotourism is located in Singapadu Village,Sukawati District, Gianyar Regency. This research discusses the financialperformance of Yoga Barista Agrotourism using financial ratio analysis anddiscriminant analysis (Z-score), as well as the constraints faced during the five yearsperiod from 2012 until 2016. The constraints faced by Yoga Barista Agrotourism werediscussed descriptive-qualitatively which included internal and external constraints. Theresults of this research were that the ratio analysis showed during the year 2012 until theyear 2016, Yoga Barista Agrotourism has a good financial performance. Atlman Zscoremodel analysis showed that in 2012 the Yoga Barista Agrotourism was categorizedinto a gray area and 2013 until 2016 was categorized into healthy category.Constraintsfaced in running the Yoga Barista Agrotourism were internal constraints such asconstraints of working hours and services and external constraints such as civet coffeeproduct supply, land conversion and tourist visit season. Yoga Barista Agrotourism couldimprove financial performance and business health by improving management andimproving business performance.